Tantangan Dan Peluang Dalam Penelitian Anti-Money Laundering Dengan Pendekatan Bibliometric Approach - Faizah, Yustin Nur; Priyono, Fri Medistya Anke; Toyyib, Moh; Sakti, Eklamsia (Jurnal Riset AKuntansi dan Bisnis, 2024)
This study aims to provide research opportunities for further research related to anti-money laundering actions. This research uses a bibliometric approach. After going through a purposive sampling selection process, 113 journals or articles were sampled for journals or articles. Data sources are from journals and articles published in Science Direct, Emerald Insight and Google Scholar. The search results show that Emerald Insight is the source of the most reviews or articles. The type of research that is often done is qualitative research with a literature review approach. 2019 was the year that gave the most reviews or articles. The United Kingdom (UK) is the subject country that performs this research the most. The Journal of Money Laundering Control is the most widely published. The Financial Action Task Force (FATF) is an area frequently covered in research. Journals are the most widely used source of data. Governmental and international regulations are urgently needed to enforce cases of money laundering and terrorist financing. Technology as a means of detection and prevention as well as the concept of AML is often used as a research object. This research provides knowledge and potential for future research.